Impact of School-based Oral Health Education on Knowledge, Practice of School Children - Makhdoom, Shazia; Malik, Liaquat Ali; Mohammad, Samrina (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the effect of verbal and audiovisual methods of dental health education on knowledge, practice of old school-going children.Study Design: Prospective longitudinal study.Place and Duration of Study: Islamia collegiate Middle School for Boys, Peshawar Pakistan, from Dec 2019 to Feb 2020.Methodology: The study population consists of 272 middle school children aged 10-13 years. After collecting baseline data which consists of a questionnaire regarding knowledge and attitude about oral hygiene followed by recording plaque score,and gingival score, students were randomly allocated into three groups. Group-1 participants received verbal dental health education through charts and pamphlets about oral health, hygiene, and tooth brushing demonstrations. Group-2 received verbal and audio-video sessions about oral hygiene. Group-3(Control-Group) received no intervention. After the intervention,knowledge attitude and plaque score gingival score was assessed.Results: A statistically significant positive change in dental knowledge and practice score was found in the AudiovisualGroup as compared to the Verbal-Group. Post-intervention mean plaque score of the participants was lowered more in the Audiovisual-Group than in the Verbal-Group. In addition, the post-intervention mean gingival score of the participants was lowered more in the audiovisual group than in the verbal group.Conclusion: Short-term oral health education programs, including A-V aids, may be useful in improving oral hygiene and gingival health.